Observing Communication Media: Defenders of Audience and Media Watch in Media Criticism context - Damas, Susana Herrera (Anagramas Rumbos y Sentidos de la Comunicación, 2014)
Nowadays, when thinking about communication media, it is very common to refer to a discouraging panorama of crisis, in which some journalists’ vices seem difficult to erradicate. In the last twenty-five years, however, together with this perception, it has also emerged a growing tendency for solving this situation, which makes us think that, no matter the situation, there is a light at the end of the tunnel. The objective of this article is to describe two of these solution ideas: audience’s defenders and media watch. Both are mechanisms which can be placed in the bigger context of media criticism and characterized by their idea for increasing media quality. The existence of each one of these mechanisms as well as the possibility for them to live together performing a hard work for making institutional media more democratic and transparent are described in the following pages.
Keywords: Public editor; media watch; audience; ombudsman; journalistic ethics; media criticism